Phytochemical Compositions of the Essential Oil from Blumea balsamifera - Li, Yu-Xian; Pei, Xiao-Hong; Jiang, Dong-Qing; Yuan, Ke (Asian Journal of Chemistry, 2013)
To analyze the chemical constituents of the volatile oil in the green peel of Blumea balsamifera. The chemical constituents was extracted from the Blumea balsamifera by HS-SPME. The components of phytochemical constituents of the volatile oil separated and identified by GC-MS. The relative content of each component was determined by area normalization. Seventy-one kinds of components were separated. Among them, 67 components were identified, accounting about 98.56 % of the total chemical constituents, most of that belong to sesquiterpenoids, the main chemical constituents of the Blumea balsamifera are compounds 1: caryophyllene (26.47 %); compound 2: thujopsene-I3 (14.45 %); compound 3: 1,7,7-trimethyl-(1S-endo)-bicyclo[2.2.1]heptan-2-ol (9.07 %); compound 4: 3-t-butyl-4-methoxyphenol methyl derivative (6.91 %); compound 5: 1R, 4R, 7R, 11R-1, 3, 4, 7-tetramethyltricyclo[5.3.1.0(4,11)]undec-2-ene (6.03); compound 6: caryophyllene oxide (5.38 %); compound 7: 1-methyl-3-(1-methylethyl)-benzene (2.89 %); compound 8: 1,1,4,8- tetramethyl-cis,cis,cis- 4,7,10- cycloundecatriene (2.36 %) etc. This experimental result enhances the understanding of phytochemical constituents of volatile oils in Blumea balsamifera and provides further reference for the development and utilization of the natural medicinal resource.